A Low Dose of Plain or Hyperbaric Bupivacaine for Unilateral Spinal Anesthesia. Issue 6 (1st November 2000) - Kuusniemi, Kristiina S.; Pihlajamäki, Kalevi K.; Pitkänen, Mikko T.
Abstract : Background and Objectives: Unilateral spinal anesthesia may be advantageous, especially in the outpatient setting. A low dose of anesthetic solution, pencil-point needle, low speed of intrathecal injection, and a lateral position have been reported to facilitate the production of unilateral distribution of spinal anesthesia. We compared the effects of plain and hyperbaric bupivacaine in attempting to obtain a unilateral spinal anesthesia for patients undergoing outpatient knee arthroscopy. Methods: Sixty patients were randomly allocated to 2 groups to receive either 1.2 mL (6 mg) of plain 0.5% bupivacaine (group 1; n = 30) or 1.2 mL (6 mg) of hyperbaric 0.5% bupivacaine in 8% glucose (group 2; n = 30). Drugs were administered at the L2-3 interspace with the patient in the lateral position. Patients remained in this position for 20 minutes before being turned supine for the operation. Spinal block was assessed by pinprick and modified Bromage scale and compared between the operated and nonoperated sides. Results: There was a significant difference between the operated and nonoperated side in both groups at all testing times, but a more unilateral spinal block was achieved with hyperbaric bupivacaine. Unilateral motor and sensory block was observed in 25 patients in group 2 (83%) and in 11 patients in group 1 (37%) ( P < .01). The hemodynamic changes were minimal, since hypotension occurred only in 5.0% and bradycardia in 1.7% of all patients. Conclusion: In conclusion, the spinal anesthesia in both groups are suitable alternatives for adult outpatient knee arthroscopies, but hyperbaric bupivacaine provides us with a more unilateral spinal block.